The role of target location on the interaction between postural balance mechanisms and end-effector performance in the tennis serve - Jamkrajang, P.; Limroongreungrat, W.; Robinson, M.; Vanrenterghem, J. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of this study was to evaluate the relationship between end-effector (tennis racket) performance and postural balance across 4 serving locations. Eleven right-handed experienced tennis players participated in this study. Participants completed 10 successful tennis serves each to 4 serving locations. 12 optoelectronic cameras at 200 Hz (BTS bioengineering, Milan, Italy) were used to collect whole-body kinematic data. Statistical parametric mapping (SPM) with regression was used to identify the relationship between postural balance control (extrapolated centre of mass displacement and changes in arms/trunk angular momentum in forward/backward direction; 1D data) and end-effector performance (maximum racket forward velocity, 0D data) across the four serving locations. The results showed no systematic relationship between postural balance control mechanisms and end-effector performance across 4 different serving locations. It was concluded that serving to different locations likely involves different balance control mechanisms to adjust for target-specific serve technique constraints. For practical application, we found no evidence that balance control and end-effector performance are tightly related within elite tennis serve performance and that these could be trained separately.